Gastroepiploic Lymph Node Flap Harvest for Patients With Lymphedema: Minimally Invasive Versus Open Approach. (July 2020) - Manrique, Oscar J.; Bustos, Samyd S.; Kuruoglu, Doga; Yan, Maria; Ciudad, Pedro; Forte, Antonio J.; Chen, Hung-chi
Abstract : Background: Vascularized gastroepiploic lymph node flaps have become a popular option to treat patients with extremity lymphedema. Overall, 2 surgical approaches to harvest this flap have been described: laparoscopic and open. In this study, we analyzed complications, harvesting time, and patient satisfaction scores, comparing these 2 techniques. Methods: Between 2012– and 2018, all patients with extremity lymphedema and candidates for the gastroepiploic flap harvest were included. Two groups were compared: open and laparoscopic approaches. Flap harvest time, postoperative pain, complications, return of gastrointestinal motility, time to discharge, and patient satisfaction scores were assessed. Results: A total of 177 patients were included, of which 126 underwent laparoscopic harvest and 51 patients underwent open approach. Only 2 patients in the laparoscopic group had prior abdominal surgery not related to cancer treatment compared with 7 patients in the open approach ( P < 0.01). Average surgical completion time for the laparoscopic versus open approach was 136 and 102 minutes, respectively ( P < 0.02). Postoperative complications for the laparoscopic versus open were as follows: 1 patient developed pancreatitis and 2 developed ileus in the laparoscopic approach, whereas 3 patients developed ileus, 1 developed small bowel obstruction, 2 developed superficial site infection, and 1 developed minor wound dehiscence in the open approach. No patient required further surgical intervention. Average return of gastrointestinal function was 1 day (laparoscopic) and 2 days (open), respectively. On a pain scale, pain scores at postoperative day 1 and upon discharge were on average 3 versus 7 and 2 versus 5, respectively ( P < 0.05). Lengths of hospital stay were on average 2 days in the laparoscopic group and 5 days in the open group ( P < 0.001). Patient satisfaction scores based on pain and scars were significantly better in the laparoscopic group versus open group ( P < 0.03). Conclusions: These data support that a minimal invasive approach is ideal and efficient when resources are available. In addition, the lower complication rate and high patient satisfaction scores give promising feedback to continue offering this technique. Abstract : Supplemental digital content is available in the text.